The degree of biology and environmental teachers practices of creative thinking skills in Northeastern Badia Directorate of Education - Alserhan, Khaled Jezza (Journal of Curriculum and Teaching Methodology, 2022)
The study aimed at exploring the degree of biology and environmental teachers practices of creative thinking skills in Northeastern Badia Directorate of Education. The population of the study was 117 male and female teachers who teach the 9th and 10th grade. To achieve the purpose of the study the researcher used a questionnaire which consisted of 63 items. The findings of the study revealed that the overall degree practices of biology and environmental teachers of creative thinking skills and in the domains of; freedom of expression, assessment strategies, classroom environment, creativity reinforcement, positive attitudes toward creativity and the teaching strategies was high. The findings of the study also showed that there are no significant differences on the teachers practices in the creative thinking skills due to the variable of gender, experience, and qualification.
Keywords: Creative thinking; Science and Biology teachers; Science